Dendritic cell‐derived TGF‐β mediates the induction of mucosal regulatory T‐cell response to Helicobacter infection essential for maintenance of immune tolerance in mice. Issue 6 (6th October 2020) - Owyang, Stephanie Y.; Zhang, Min; El‐Zaatari, Mohamad; Eaton, Kathryn A.; Bishu, Shrinivas; Hou, Guoqing; Grasberger, Helmut; Kao, John Y.
Abstract: Background: Helicobacter pylori infection leads to regulatory T‐cell (Treg) induction in infected mice, which contributes to H. pylori immune escape. However, the mechanisms responsible for H. pylori induction of Treg and immune tolerance remain unclear. We hypothesized DC‐produced TGF‐β may be responsible for Treg induction and immune tolerance. Materials and Methods: To test this hypothesis, we generated TGF‐β ∆DC mice (CD11c + DC‐specific TGF‐β deletion) and assessed the impact of DC‐specific TGF‐β deletion on DC function during Helicobacter infection in vitro and in vivo. To examine the T cell–independent DC function, we crossed TGF‐β ∆DC mice onto Rag1KO background to generate TGF‐β ∆DC xRag1KO mice. Results: When stimulated with H. pylori, TGF‐β ∆DC BMDC/splenocyte cocultures showed increased levels of proinflammatory cytokines and decreased levels of anti‐inflammatory cytokines compared to control, indicating a proinflammatory DC phenotype. Following 6 months of H. felis infection, TGF‐β ∆DC mice developed more severe gastritis and a trend toward more metaplasia compared to TGF‐β fl/fl with increased levels of inflammatory Th1 cytokine mRNA and lower gastric H. felis colonization compared to infected TGF‐β fl/fl mice. In a T cell–deficient background using TGF‐β ∆DC xRag1KO mice, H. felis colonization was significantly lower when DC‐derived TGF‐β was absent, revealing a direct, innate function of DC in controlling H. felis infection independent of Treg induction. Conclusions: Our findings indicate that DC‐derived TGF‐β mediates Helicobacter ‐induced Treg response and attenuates the inflammatory Th1 response. We also demonstrated a previously unrecognized innate role of DC controlling Helicobacter colonization via a Treg‐independent mechanism. DC TGF‐β signaling may represent an important target in the management of H. pylori .